3D Printing in Copious Forensic Odontology Among Medical Professionals - Pawan Kumar Earasi, Dr. Abirami Arthanari (Drugs and Cell Therapies in Hematology, 2021)
Introduction: The phrase "3D printing" refers to a manufacturing technique that involves building items one layer at a time and then assembling them into a finished object. Rapid prototyping is another name for this method, which is more properly defined as additive manufacturing. Aim: Use of 3D printing in copious forensic odontology among medical professionals Materials and Methods: To evaluate knowledge and awareness of 3D printing in copious forensic odontology among medical professionals through a survey/ questionnaire. The questionnaire was reviewed and amendments were made to improve clarity of pertinent questions and eliminate ambiguous responses. The survey instrument was a structured questionnaire with both open and close ended questions. Results: There are various types of 3D printing technologies which are used in the current century. 38.18% of the participants were aware of material jetting (MJ) (Polyjet) and material extrusion (or fused deposition modeling, FDM), 61.82% were aware of vat polymerization(e.g.,stereolithography, SLA) and binder jetting (BJ). Conclusion: 3D imaging and modelling, as well as CAD technology, are having a significant influence on all parts of dentistry. From this digital data, 3D printing allows for the precise creation of one-of-a-kind, complicated geometrical shapes in a range of materials, either locally or in industrial centres. Even while a 3D printer can currently create almost everything we make for our patients, no one technology can meet all of their demands. Keywords: forensic odontology, medical professional, 3D printing, innovative technique